Saudi Novel: Commencements, Efforts, and Headway (2) - Dahami, Yahya (Hasanuddin University, 2025)
The Saudi novel has undergone notable changes in both subject matter and creative growth. The Saudi novel, through a variety of stages in its evolution, might help readers comprehend the nature of aesthetic improvement carried out at each stage. The study seeks to illuminate the significance of the important genre of literature; it is Saudi fiction by displaying the onsets, growth, as well as its development. In keeping with the nature of the literary investigation, the researcher applies the analytical-critical approach in this paper. It begins with a brief introduction to the Arabic novel before moving on to discuss the following topics: the Saudi Literacy Movement, Saudi Novel: A Glimpse, and an instance of the early challenges to Saudi narratives. It is The Resurrection, the Second Saudi Novel by Maghrabi. The investigation comes to an end with the discussion and the conclusion.